ANALYSIS OF FORECAST OF RENEWABLE ENERGY DEVELOPMENT IN NORTH SUMATRA USING ANFIS - Nugraha, Yoga Tri; Simanjuntak, Puan Maharani; Irwanto, Muhammad; Rida, Rizkha; Othman, M.A. (Jurnal Media Elektro, 2024)
The transition towards renewable energy sources is critical for sustainable development, particularly in regions like North Sumatra, Indonesia, where energy demand is increasing rapidly. This research presents an analysis of the forecast of renewable energy development in North Sumatra using the ANFIS. The analysis begins with data collection and preprocessing, incorporating historical data on energy consumption, renewable energy installations, population growth, economic indicators, and environmental factors. ANFIS models are then developed and optimized to capture the complex relationships between these variables and forecast renewable energy trends accurately. Model validation and performance evaluation techniques ensure the reliability of the forecasted outcomes. The results of the calculations conducted using the ANFIS method obtained an error value of 0,000201092% and has a Forecast of Renewable Energy Development in North Sumatra in 2028 of 160.44 MW.